Home-deliveries before-during COVID-19 lockdown: Accessibility, environmental justice, equity, and policy implications. (April 2021) - Figliozzi, Miguel; Unnikrishnan, Avinash
Highlights: Analysis of home delivery access before and during COVID-19 lockdown. Underserved populations access decreased during the lockdown. Develop the concept of home-based accessibility. Analysis of home delivery equity and environmental justice issues. Discussion of policy ideas to ameliorate home delivery inequalities. Abstract: During the COVID-19 lockdowns, home deliveries have changed from being a desirable luxury or comfortable solution to a health-supporting and essential service for many COVID-19 at-risk populations. However, not all households are equal in terms of access to home deliveries. The onset of COVID-19 has brought to light access inequalities that preceded the pandemic and that the COVID-19 lockdown has exacerbated and made visible. The concept of home-based accessibility (HBA) is introduced, and novel research questions are addressed: (i) What type of households had zero home deliveries before COVID-19 lockdown? (ii) How the COVID-19 lockdown affected the type of households that receive home deliveries? and (iii) What are the implications of no access to home delivery services in terms of equity and environmental justice? To answer the first two questions, exploratory and confirmatory models with latent variables are estimated utilizing data collected from an online survey representative of the population in the Portland metropolitan region. Policy and environmental equity implications are discussed using the concept of home-based accessibility (HBA). The results indicate that traditionally underserved populations are less likely to benefit from home-based delivery services and that COVID-19 has worsened home delivery inequalities for underserved populations.